Numerical simulation of compressive failure of carbon-fiber-reinforced plastic laminates with various hole shapes. (2nd January 2021) - Shimizu, Satoko; Sato, Mio; Koyanagi, Jun; Suemasu, Hiroshi; Kogo, Yasuo
Abstract : The effect of stress concentration on the compressive failure behavior of a carbon fiber composite laminate with an open hole is experimentally and numerically studied. The aspect ratio of the elliptical hole is varied to investigate the dependence of the failure behavior on the stress concentration. A finite-element analysis is implemented using ABAQUS 2017, and a dynamic explicit solving method is adopted. Continuum shell elements incorporating Hashin's failure criteria and cohesive interaction, which is a combined function of a general contact definition and cohesive traction-separation law, are used to model the damage growth of a lamina and interlaminar, respectively. The damage initiations are defined by critical stresses, and damage evolutions are defined by energy assumptions of softening behavior for continuum shell elements and cohesive interaction. The numerical results of the stresses at initial damage occurrences and ultimate failures agree well with the experimental results for the specimens with various aspect ratios. In addition, the numerical and experimental results of the damage behavior of the 0° ply are in good agreement. Internal damage and delamination behavior that are difficult to observe in experiments are also discussed based on the numerical results.